Artificial hybridization techniques in small millets—A review - Nagaraja, T. E.; Nandini C.,; Bhat, Sujata; Parveen S., Gazala (Frontiers in Plant Science, 2023)
Small millets are nutri-rich, climate resilient food and fodder crops. They include finger millet, proso millet, foxtail millet, little millet, kodo millet, browntop millet and barnyard millet. They are self-pollinated crops and belong to the family poaceae. Hence, to widen the genetic base, creation of variation through artificial hybridization is a pre requisite. Floral morphology, size and anthesis behavior cause major hindrance in recombination breeding through hybridization. Manual emasculation of florets is practically very difficult; therefore, contact method of hybridization is widely followed. But, success rate of obtaining true F1s is 2 to 3%. In finger millet, hot water treatment (52 ᵒC) for 3 to 5 minutes causes temporal male sterility. Chemicals such as maleic hydrazide, gibberellic acid and ethrel at different concentrations aid in inducing male sterility in finger millet. Partial sterile lines (PS) developed at Project Coordinating unit, Small millets, Bengaluru are also in use. The % seed set in crosses derived from PS lines ranged from 27.4 to 49.4, with an average of 40.10%. In proso millet, little millet and browntop millet apart from contact method, hot water treatment, hand emasculation and USSR method of hybridization are also followed. Newly developed modified crossing method known as SMUASB (Small Millets University of Agricultural Sciences Bengaluru) method in proso and little millet has a success rate of 56 to 60% in obtaining true hybrids. Hand emasculation and pollination under green house and growth chamber in foxtail millet with a success rate of 75% seed set is suggested. In barnyard millet, hot water treatment (48 to 52 ᵒC) for 5 minutes followed by contact method is often practiced. Kodo millet being cleistogamous, mutation breeding is widely followed to create variation. Most commonly, hot water treatment is followed in finger millet and barnyard millet, SMUASB in proso and little millet. Although, no specific method is suitable for all small millets, it is essential to identify a trouble-free technique that produces maximum crossed seeds in all the small millets.